1999
DOI: 10.1093/jac/43.5.659
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth-mediated disruption of the glycocalyx- cell wall of Helicobacter pylori:ultrastructural evidence for a mechanism of action for bismuth salts

Abstract: The mechanism of bismuth's bactericidal activity against Helicobacter pylori was investigated using transmission electron microscopy (TEM) and analytical electron microscopy (AEM); time-kill kinetic methods evaluated the effect of excess divalent cations. TEM analysis of untreated H. pylori revealed a normal morphology. In contrast, H. pylori exposed to bismuth salts had swollen, distorted cells with membrane-cell wall blebbing and a cytoplasm containing electron-dense, sometimes crystalline aggregates. By AEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
0
24
0
2
Order By: Relevance
“…However, our hypothesis that the antimicrobial action of bismuth was due to the inhibition of iron uptake was challenged by unchanged intracellular iron levels in two of the three H. pylori strains following culturing in the presence of this bismuth compound. Bismuth-induced changes in H. pylori morphology have been seen before (11,45,47), but our observations of accompanying changes in outer membrane protein and LPS profiles are new. The bismuth-induced changes included the up-regulation of a 12-kDa protein and two proteases and diminished LPS expression and are identical to those observed in other studies in which H. pylori was grown under iron-limiting conditions (9,29).…”
Section: Discussionmentioning
confidence: 53%
“…However, our hypothesis that the antimicrobial action of bismuth was due to the inhibition of iron uptake was challenged by unchanged intracellular iron levels in two of the three H. pylori strains following culturing in the presence of this bismuth compound. Bismuth-induced changes in H. pylori morphology have been seen before (11,45,47), but our observations of accompanying changes in outer membrane protein and LPS profiles are new. The bismuth-induced changes included the up-regulation of a 12-kDa protein and two proteases and diminished LPS expression and are identical to those observed in other studies in which H. pylori was grown under iron-limiting conditions (9,29).…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, it possess antibacterial effects by inhibiting various enzymes produced by H. py Data are presented as n (%) with 95% CI. See Table 1 lori (including urease, catalase, and lipase/phospholipase), preventing adhesion of H. pylori to surface epithelial cells, and inhibiting ATP synthesis and some membrane functions in H. pylori [20][21][22]. It has been reported that the addition of bismuth to standard triple therapy improved the eradication rate [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Manhar18 reported that Bi 3+ possesses antimicrobial activity against a wide range of bacteria, particularly Helicobacter pylori. When exposed to bismuth salts H. pylori cells become swollen and distorted and exhibit membrane–cell wall blebbing 31, 32. Therefore, it seems reasonable to employ bismuth as an antimicrobial component in pulp‐capping cement.…”
Section: Discussionmentioning
confidence: 99%